Long-term impact of Diabetes Prevention Program interventions on walking endurance - Munshi, Medha N.; Venditti, Elizabeth M.; Tjaden, Ashley H.; Knowler, William C.; Boyko, Edward J.; Middelbeek, Roeland J. W.; Luchsinger, José A.; Lee, Christine G.; Hazuda, Helen P.; Salive, Marcel E.; Edelstein, Sharon L.; Storer, Thomas W. (Frontiers in Public Health, 2024)
ObjectivesType 2 diabetes (T2D) and prediabetes are associated with poor walking endurance, a marker of physical function. We aimed to examine the long-term effects of metformin or intensive lifestyle intervention in adults at high risk of T2D on their 6-min walk test (6MWT) performance.MethodsParticipants were randomized in the 3-year Diabetes Prevention Program (DPP) to one of the three groups: lifestyle intervention, metformin, or placebo, and were subsequently followed in the DPP Outcomes Study. A 6MWT was conducted 20 years after randomization. Associations between DPP interventions and 6MWT completion (achieving a distance ≥200 m) were assessed using logistic regression. Among the test completers, differences in distance walked (6MWD) were evaluated using multivariable linear regression. Additional variables of interest included concomitant measures of body mass index (BMI) and grip strength along with mean measures of HbA1c and self-reported physical activity (PA).ResultsData on 1830 participants were analyzed. The interventions were not associated with test completion or the 6MWD among test completers (362, 364, and 360 m in the lifestyle, metformin, and placebo groups, respectively, p = 0.8). Age, education, grip strength, and PA were each significantly associated with the 6MWT completion and the 6MWD after adjustment. Grip strength, PA, and education were positively associated with the 6MWD, while age, BMI, and HbA1c were negatively associated with the 6MWD.ConclusionWe confirmed that the 6MWT is related to other measures of physical ability such as PA and grip strength in persons at risk for and with T2D, suggesting potential long-term benefits of maintaining a healthy lifestyle. However, we did not observe a sustained effect of the original randomized interventions.Clinical trial registrationhttp://www.clinicaltrials.gov/ct/show/NCT00004992, identifier DPP NCT00004992; http://www.clinicaltrials.gov/ct/show/NCT00038727, identifier DPPOS NCT00038727